Approaches for controlling sea lice infestation in global salmon farming: What is applicable in Canadian aquaculture industry. Issue 4 (1st October 2016) - Yossa, Rodrigue; Dumas, André
ABSTRACT: This article describes the sea lice control methods that are currently applicable to salmon farming in Canada. Three commercial chemical products are approved for use against sea lice in Canada: Slice®, Interox® Paramove® 50, and Calicide®. Physical control methods include photoperiod and cage-depth manipulations, desiccation of farm equipment, and the use of electric fences. Biological control measures include the polyculture of salmon with wrasse or mussel. Nutraceuticals and immunostimulants shown to reduce sea lice infestations in salmon include unmethylated DNA, yeast fermentation extract-Brewer's yeast compound, AllBrew and NuPro, MacroGard®, and Optimûn®. Salmon farmers are recommended to use site-specific integrated approaches, by properly adapting a combination of chemical, physical, biological, and nutritional measures to the environmental and financial characteristics of their farm. In the future, development of vaccines against sea lice and of salmon lines resistant to sea lice will play a pivotal role in fighting against this parasite.